2014
DOI: 10.1177/0959353514539652
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the concept of consent for anti-sexual violence activism and education

Abstract: Sexual violence prevention has shifted from centering around a message of 'no means no' toward a message of 'get consent.' This paper explores how young adults conceptualise consent in relation to how they talked about expressing a willingness to participate in sex. The analysis here argues that understandings of consent are disconnected from how young people understand communication about sex. Consent is viewed as a formal minimum requirement for 'ok' sex. At the same time, young people were more sophisticate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(145 citation statements)
references
References 29 publications
6
132
1
6
Order By: Relevance
“…In some respects, research has identified this concept of consent as ongoing (Beres, 2010;Beres, 2014;Humphreys, 2004) and that some educators and scholars have identified important skills needed to assess for consent in an ongoingmanner (Jozkowski, 2015;Pineau, 1989). Some educators are also designing (Carmody, 2015) and assessing (Carmody, 2015) programs that begin to address these complexities, supplying skills for seeking and giving clarity in sexual encounters in an ongoing way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some respects, research has identified this concept of consent as ongoing (Beres, 2010;Beres, 2014;Humphreys, 2004) and that some educators and scholars have identified important skills needed to assess for consent in an ongoingmanner (Jozkowski, 2015;Pineau, 1989). Some educators are also designing (Carmody, 2015) and assessing (Carmody, 2015) programs that begin to address these complexities, supplying skills for seeking and giving clarity in sexual encounters in an ongoing way.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have identified consent as an ongoing, continuous process (Beres, 2014;Humphreys, 2004). Consent is something given or obtained and can be renewed as sexual behavior continues.…”
Section: Humphreysmentioning
confidence: 99%
“…The change from "no means no" to the message of "get consent" caused several scholars analyze how young adults conceptualize consent (Beres, 2014). Worried for sexual violence prevention, education, and research on sexual consent, Beres studies the understanding of consent, from a perspective based on "communication about sex" and not only "ok sex."…”
Section: Beyond Words Defining Consent and Asking For Its Regulationmentioning
confidence: 99%
“…In order to address some of the unique circumstances that college students experience, many institutions of higher education have created prevention programs targeting sexual violence and policies around the concept of consent. Prevention programs include educational programs such as facilitated lectures and workshops as well as educational materials designed to increase awareness (Beres, 2014). These interventions have demonstrated outcomes such as increased awareness of rape myths, increased empathy for victims, increased sexual assault awareness, and increased bystander behavior (Bradley, Yeater, & O'Donohue, 2009;Foubert, Godin, & Tatum, 2010;Hanson & Gidycz, 1993).…”
Section: Consent At the Community Levelmentioning
confidence: 99%
“…The majority of U.S. high schools provide abstinence-only education that tend to not be inclusive, often include inaccurate information, and do not address consent (Kantor et al, 2008;Muehlenhard et al, 2016). While many institutions of higher education have implemented facilitated lectures, workshops, and educational campaigns to increase awareness of sexual assault and consent, none have demonstrated outcomes specific to consent (Beres, 2014). In addition, many of these programs do not reflect the sexual scripts of college students and do not clearly define what constitutes consent (Johnson & Hoover, 2015;Muehlenhard et al, 2016;Reynolds, 2004).…”
Section: Consent At the Individual Levelmentioning
confidence: 99%